Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones), based on a new species from the Chapada Diamantina relict cloud forests, Brazil - Araujo-Da-Silva, Luiz Paulo; Desouza, Adriano Medeiros; Dasilva, Marcio Bernardino (Zootaxa, 2020)
In this paper, we describe a new subfamily of Gonyleptidae, Paragoniosomatinae subfam. nov., based on a new genus and species, Paragoniosoma cachaceiro gen. nov., sp. nov., found in an upper montane cloud forest of Chapada Diamantina mountains, one of the small interior patches of Atlantic Forest. This discovery suggests that the narrow-restricted cloud forests are old relicts of an Atlantic Forest hotspot. Paragoniosoma cachaceiro gen. nov., sp. nov. is characterized by the presence of four areas on the dorsal scutum, serose dry mark in areas III–IV, seven basal setae in penis (macrosetae A and B) in two rows, and very large tarsal process. We performed a phylogenetic analysis based on morphological characters that revealed a close relationship of the new species with Goniosomatinae, a subfamily that includes six genera and 38 valid species distributed throughout the coastal Atlantic Forest. The new species also has the same habitat and other behavioural and ecological traits as Goniosomatinae, furnishing great insights on the evolution of their characteristic biology, e.g., subsocial behavior. Field surveys of harvestmen from the type locality and nearby lowland seasonal forests indicate a unique fauna, including additional new, undescribed species. In addition to phylogenetics, this dissimilarity with other regions and the presence of endemic species of other animal and plant taxa provide support for the consideration of the cloud montane patches of Chapada Diamantina as relicts. We discuss this rule in the historical biogeographic context of Atlantic Forest and suggest that the new species represents evidence of an Atlantic Forest that was more widespread in the past.